The PGPR mechanisms of salt stress adaptation and plant growth promotion - Shultana, Rakiba; Tan, Ali Kee Zuan; Naher, Umme Aminun; Mominul Islam, A. K. M.; Rana, Md. Masud; Rashid, Md. Harun; Irin, Israt Jahan; Islam, Shams Shaila; Rim, Adiba Afrin; Hasan, Ahmed Khairul (Multidisciplinary Digital Publishing Institute, 2022)
Worldwide crop productivity hampers severely due to the adverse effects of salinity. Global warming causes a rapid escalation of the salt-affected area, and new agricultural land is affected through saltwater intrusion. The ever-growing human population impulses to utilize the saline area for crop cultivation to ensure food security. Salinity resistance crops could be a promising substitute but with minor success because inappropriate tactics on saline soil management resulted in unsatisfactory yield. Salt-tolerant plant growth-promoting rhizobacteria (ST-PGPR) is considered an alternate way towards enhancing crop growth in saline ecosystems. It is reported that PGPR is enabled to produce exopolysaccharides which lead to biofilm formation and generate osmoprotectants and antioxidant enzymes that can significantly contribute to stimulating plant growth in the saline ecosystem. In addition, several plant growth-promoting characteristics of PGPR such as the acquisition of essential nutrients and upsurge hormone production could enhance plant growth simultaneously. In this review, we will explore the survival mechanisms of ST-PGPR and their influence on plant growth promotion in saline ecosystems.